Human cortical activity correlates with stereoscopic depth perception. - Backus, B; Fleet, D; Parker, A; Heeger, D (2001)
Stereoscopic depth perception is based on binocular disparities. Although neurons in primary visual cortex (V1) are selective for binocular disparity, their responses do not explicitly code perceived depth. The stereoscopic pathway must therefore include additional processing beyond V1. We used functional magnetic resonance imaging (fMRI) to examine stereo processing in V1 and other areas of visual cortex. We created stereoscopic stimuli that portrayed two planes of dots in depth, placed symmetrically about the plane of fixation, or else asymmetrically with both planes either nearer or farther than fixation. The interplane disparity was varied parametrically to determine the stereoacuity threshold (the smallest detectable disparity) and the upper depth limit (largest detectable disparity). fMRI was then used to quantify cortical activity across the entire range of detectable interplane disparities. Measured cortical activity covaried with psychophysical measures of stereoscopic depth perception. Activity increased as the interplane disparity increased above the stereoacuity threshold and dropped as interplane disparity approached the upper depth limit. From the fMRI data and an assumption that V1 encodes absolute retinal disparity, we predicted that the mean response of V1 neurons should be a bimodal function of disparity. A post hoc analysis of electrophysiological recordings of single neurons in macaques revealed that, although the average firing rate was a bimodal function of disparity (as predicted), the precise shape of the function cannot fully explain the fMRI data. Although there was widespread activity within the extrastriate cortex (consistent with electrophysiological recordings of single neurons), area V3A showed remarkable sensitivity to stereoscopic stimuli, suggesting that neurons in V3A may play a special role in the stereo pathway.